Depth estimation from a single image using defocus cues - Chan, P. P. K.; Bing-Zhong Jing; Ng, W. W. Y.; Yeung, D. S. (2011 International Conference on Machine Learning and Cybernetics, 2011)
Depth estimation from a single image is a challenging problem in computer vision research. By analyzing the defocus cues produced by the depth of field of lens, the information of depth can be determined. We employ reverse heat equation, which is simple and effective, for this analysis. Because the depth map is required to be smooth in many applications, a mean shift segmentation and graph cut based method is proposed to infer the depth map of the scene. The confidence of depth estimation is incorporated into the energy function of graph cut to preserve details of the depth map. Experimental results show that the proposed method can produce a good depth map even from a single image.